Cattle reproductive performance in the Paiaguás subregion of the Brazilian Pantanal II. effect of mineral supplementation on heifers’ reproductive rates - Pott, Edison Beno; Tullio, Rymer Ramiz; Almeida, Irajá Loureiro de; Brum, Paulo A. R. de; Sousa, Júlio Cesar de (Pesquisa Agropecuaria Brasileira, 2014)
The effects of mineral supplementation (common salt= SC, SC + dicalcium phosphate = SP and SP + sulphur + micronutrients = SPM) on Zebu heifers reproductive performance were studied in native pastures in the Pantanal Mato-grossense, Brazil. A completely randomized design was used. The experiment was iniciated in February 1980, with weaned heifers, and concluded in February 1986. Mineral supplementation treatments - SC, SP and SPM, respectively - did not Influence (P>0,05) 1) the interval between first and second calvings (528, 489, and 510 days); 2) the average number of calves born (2.07, 2.21, and 2.17) and weaned (1.73, 2.07, and 1.90); 3) the calving rate (65.6%, 70.3%, and 68.9%); and 4) the weaning rate (57.8%, 70.3%, and 66.7%). However it increased the cows' weight at weaning, 20 kg to 30 kg higher in treatments containing dicalcium phosphate (DP). Considering the weight responses to DP and the better performance tendencies observed on animals of treatment SP, it was concluded that other deficiencies - possibly nitrogen - and/or pasture quality and quantity seasonal variation limited mineral influence.